«Croissez et multipliez-vous»: la formation de chercheurs dans les centres de recherche en sciences de l'humain et du social - Legault, Marie-Josee (Canadian Journal of Higher Education, 1993)
Research centers in the social sciences and humanities are currently being established in Quebec. Their mission is two-fold: to produce knowledge and to train researchers. A dilemma appears to be brewing between these two objectives, as the first emphasizes the kind of speedy and sustained progression that is not always possible in the second. This article will explore an ethnographic study conducted in three research centers, in an attempt to illustrate the process by which this tension can be eased. Thus, local organization of research work generates within the research personnel an interplay of segmented and graded informal mobility lines, which is a logical way to address the problem. The explanation model presented in this article exposes certain shortcomings of the Derber and Schwartz logocratic work organization model (1988) for university research centers, and proposes an interpretation of the candidate selection process, to which the logocratic model pays little attention.